Structural basis for incision at deaminated adenines in DNA and RNA by endonuclease V. Issue 2 (March 2015) - Dalhus, Bjørn; Alseth, Ingrun; Bjørås, Magnar
Abstract: Deamination of the exocyclic amines in adenine, guanine and cytosine forms base lesions that may lead to mutations if not removed by DNA repair proteins. Prokaryotic endonuclease V (EndoV/Nfi) has long been known to incise DNA 3′ to a variety of base lesions, including deaminated adenine, guanine and cytosine. Biochemical and genetic data implicate that EndoV is involved in repair of these deaminated bases. In contrast to DNA glycosylases that remove a series of modified/damaged bases in DNA by direct excision of the nucleobase, EndoV cleaves the DNA sugar phosphate backbone at the second phosphodiester 3′ to the lesion without removing the deaminated base. Structural investigation of this unusual incision by EndoV has unravelled an enzyme with separate base lesion and active site pockets. A novel wedge motif was identified as a DNA strand-separation feature important for damage detection. Human EndoV appears inactive on DNA, but has been shown to incise various RNA substrates containing inosine. Inosine is the deamination product of adenosine and is frequently found in RNA. The structural basis for discrimination between DNA and RNA by human EndoV remains elusive.